Sobralia fragrans - Alomia Aguirre, Jasmin Amparo (2018)
Epiphytic, caespitose herb, up to 25 cm tall. Roots ca. 5 mm wide. Stems 120–150 × 3–4 mm, 1-foliate; covered by a basal, acute, glumaceous sheath. Leaves elliptic, acute, plicate, 16.5–23.5 × 4.0–5.5 cm. Inforescence terminal, covered by a ovate foliar bract, with a single ephemeral and membranous fower; foral bracts concealed by a infundibuliform sheath, 1.2–2.0 × 0.6–1.8 cm; peduncle ancipitose, 16–26 cm long. Ovary terete to clavate, ca. 20 mm long, 1.8 mm wide.